The Development of Audio-Visual Learning Media based on Kenduri Laot Tradition for Students at SMA Plus Athiyah Banda Aceh City to Increase Character Values - Nina Suryana; Sufandi Iswanto; Heri Fajri (Universitas Nahdlatul Ulama Blitar, 2021)
The planting of character values in schools based on local wisdom is one of the breakthroughs that can be done by the teacher. One of them with the values the Kenduri Laot tradition that can be developed in the form of learning media. This study aims to develop a lesson plan design in the form of audio visual media-based of the Kenduri Laot tradition to improve the character of students in SMA Plus Athiyah Banda Aceh. The method used is research and development. This method refers to the model of Gall and Borg with the simplification of the stages from ten to three, namely the formulation of the problem, the designer of the development, and the effectiveness of or reflection. Based on the results of the study found a problem that during this time the planting of character values-based of the Kenduri Laot tradition is still not maximized. At this stage of development, carried out the preparation of the synopsis to test the expert audio-visual media. The results of the effectiveness of the t-Test shows that the significance value in the experimental group of 0.000 < 0.05 and in the control group amounted to 0.025 > 0.05, meaning that there is an increase of the characters in the experimental group.